1999
DOI: 10.2307/3802664
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sample Size on Kernel Home Range Estimates

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management.Abstract: Kernel methods for estimating home range are be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
835
4
21

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,124 publications
(881 citation statements)
references
References 27 publications
21
835
4
21
Order By: Relevance
“…Kernel Home Range (KHR) using Animal Movement Analysis software (Hooge & Eichelaub, 1997) and Arcview GIS (Environmental Systems Research Institute, Red¬ lands, CA), employing the ad-hoc smoothing option. This method is a fixed-kernel range estimate, and appears to be the best method for calculating range estimates from location data (Seaman & Powell, 1996, Seaman et al, 1999, Kernohan et al, 2001. We used these estimates of area to calculate the den¬ sity of 95% of the estimated herd size (665 000).…”
Section: Methodsmentioning
confidence: 99%
“…Kernel Home Range (KHR) using Animal Movement Analysis software (Hooge & Eichelaub, 1997) and Arcview GIS (Environmental Systems Research Institute, Red¬ lands, CA), employing the ad-hoc smoothing option. This method is a fixed-kernel range estimate, and appears to be the best method for calculating range estimates from location data (Seaman & Powell, 1996, Seaman et al, 1999, Kernohan et al, 2001. We used these estimates of area to calculate the den¬ sity of 95% of the estimated herd size (665 000).…”
Section: Methodsmentioning
confidence: 99%
“…As variance in x and y coordinates of orang-utan location data was unequal, they were automatically rescaled with a unit variance before applying the smoothing parameter selection. Least Squares Cross Validation (LSCV: Silverman 1986, Worton 1995) smoothing parameter selection is currently the recommended smoothing parameter selection in the ecological literature (Seaman et al 1999), but it has been found to have several drawbacks (Kernohan et al 2001). For example, LSCV was criticised for its high variability and its tendency to under-smooth location data (Horne & Garton 2006b).…”
Section: Comparing Home Range Estimatorsmentioning
confidence: 99%
“…Report sample size used for home range estimates Use fixed kernel rather than adaptive ones (Seaman et al 1999, Kernohan et al 2001 Use automated method for smoothing parameter selection and report smoothing parameter values Estimate ranges over biologically meaningful temporal scales and include temporally consistent periods (e.g. annual range)…”
Section: Estimating Home Range Sizementioning
confidence: 99%
“…Each individual's acceptable locations then were subject to a 5 percent outlier removal using the harmonic mean method (Dixon and Chapman 1980). We only retained data on chipmunks possessing a minimum of 28 acceptable locations for subsequent home-range analysis (Seaman et al 1999). We then used the fixed kernel method with least squares cross validation as a smoothing parameter to construct our 95 percent (home range) and 50 percent (core area) contour utilization distributions (UD) (Silverman 1986, Worton 1989.…”
Section: Home Range Analysismentioning
confidence: 99%